Effects of the vertical component of ground motion on the seismic performance of Bhakra Gravity Dam - Sevim, Baris; Altunisik, Ahmet Can; Gunaydin, Murat (TECHNO-PRESS, 2021)
In this paper, the earthquake component effects on the seismic performance of Bhakra Gravity Dam in India are investigated. For the purpose, Bhakra Dam is modeled two-dimensionally considering dam-reservoir-foundation interaction. In the finite element modeling, dam and foundation are represented by PLANE182 elements in ANSYS with different material properties, and fluid is considered with FLUID29 elements. This type of element provides translation and pressure degrees of freedom. Linear time history analyses on the dam are performed by considering components of the 1991 Uttarkashi and 1999 Chamoli (NW Himalaya) Earthquakes in India. During the analyses firstly the horizontal component of earthquakes are applied to system and results are obtained, and then both of horizontal and vertical components are applied to the systems together. In the analyses, element matrices are computed using the Gauss numerical integration technique. The Newmark method is used in the solution of the equation of motions. Also, Rayleigh damping is considered. The seismic performance of Bhakra Dam is examined and presented by dynamic characteristics, displacements, principal stresses, and demand-capacity ratios. The results showed that the vertical components of the earthquake significantly affect the response of the dam. The results show that the vertical component with the horizontal component cause biggest tensile stresses compared to only the horizontal component for both earthquakes. However, displacement response is changed depending on the ground motion. As a conclusion of this study it can be said that the vertical component changes the structural response of the dam on both of the good and bad behaviors.
Keywords: Bhakra Gravity Dam; demand-capacity curve; finite element modeling; seismic performance; vertical component; EARTHQUAKE ANALYSIS; DYNAMIC-ANALYSIS; FOUNDATION INTERACTION; CONCRETE MODEL; WATER LENGTH; BEHAVIOR; Construction & Building Technology; Engineering; Materials Science